ANALISIS KESULITAN SISWA DALAM MEMECAHKAN MASALAH FISIKA BERBENTUK GRAFIK DENGAN TES DIAGNOSTIK - ANDRIONO MANALU; JUSPEN GULTOM (JURNAL ILMIAH MAKSITEK, 2021)
This study aims to find out problem solving skills in the form of graphs and difficulty profiles, especially in straight motionmaterial. This type of research is qualitative research. This research was conducted at SMA Negeri 1 Onanrunggu in the oddsemester of the 2020/2021 school year. The subject of this study was a grade XI MIA 1 student who was able to take part inonline learning. The instruments used in this study are diagnostic tests in the form of descriptions that have passed the stageof instrument validation tests. The analysis is done using descriptive percentages. The results showed that the percentage ofeach ability began with graph interpretation capability (50.60%), predicting ability (67.86%), and transformation ability(67.63%). Students' difficulty profiles are based on KKM achievement, prerequisite knowledge, material profiles,misconceptions, and troubleshooting stages. Based on the mastery of KKM, students still have difficulty for all indicators. Forthe profile of students' difficulties based on their pre-existing knowledge, students still have difficulty in the countingoperations section. For student difficulty profiles based on material profiles, students still have difficulty for all sub-materialsespecially acceleration. As well as the latter, the student's difficulty profile is based on the stages of problem solving. Thedifficulty of students is increasing from the lowest stage, which is the stage of understanding the problem and the higheststage is the review stage.